First tip: Type your problems in a black font. It shows up much better on white. Really!

Let's take the first term of the first problem:

-2(c-d) = (-2)(c) + (-2)(-d) = -2c + 2d.

This is called the distributive law and it always works like I did it above.

So:

9) -2(c - d) + (c - d) - 6(c - d)

= (-2)(c) + (-2)(-d) + c - d + (-6)(c) + (-6)(-d)

= -2c + 2d + c - d - 6c + 6d

= -2c + c - 6c + 2d - d + 6d <-- I just rearranged the line above to group terms with c and d.

Now we can reverse the distributive law. Look at the first 3 terms:

-2c + c - 6c = (-2 + 1 - 6)c = -7c

Likewise:

2d - d + 6d = (2 - 1 + 6)d = 7d

Putting it all together:

-2(c - d) + (c - d) - 6(c - d) = -7c + 7d

See if you can do the other one:

-3(4x + -2y) - 2(x+3y) -2(2x+6y)

I got -10x - 12y.

-Dan